Espectro clínico y epidemiológico de la rinotraqueitis infecciosa bovina (1996)
ABSTRACT: IBR was recognized in Europe since the beginning of this century as a disease of the genital tract of cows. Its etiological agent was identified only in 1956 in United States, where respiratory symptoms and lesions were the cardinal markers of the disease. Other clinical forms such as encephalomyelitis, conjunctivitis and abortion, where found later. Since the 70's the virus was detected in Colombia and the infection has been prevalent. Viral isolation as well as clinical cases have been very scarce. Researches are making efforts to characterize IBR in this country. In this review we also describe the usual diagnostic technics for serologic surveys and new methods such as the Polymerase Chain Reaction (PCR) to detect the viral genome.